أثر العنف الأسري على التحصيل الدراسي لدى تلميذات الطور المتوسط - قده, نسيمة; مقرحي, صفاء (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة باللغة العربية هدفت دراستنا إلى الكشف للكشف عن علاقة العنف الأسري والتحصيل الدراسي لدى التلميذات الطور المتوسط، ولهذا الغرض اختبرت عينة قوامها 70 تلميذة يدرسن في متوسطة باهي عبد الرزاق بالرقيبة الوادي وقد تم الاعتماد على الاستبيان تحققت فيه شروط الصدق والثبات، قائم على محورين أساسيين هما: - العنف البدني الموجه نحو الأبناء داخل الأسرة وعلاقته بالتحصيل الدراسي - العنف اللفظي الموجه نحو الأبناء داخل الأسرة وعلاقته بالتحصيل الدراسي كما اتبعنا في دراستنا على المنهج الوصفي ولا ننسى كذلك مجموعة من الدراسات وبعد حساب الخصائص السيكومترية والSPSS توصلنا إلى مجموعة من النتائج بينت أنه لا يوجد تأثير للعنف الأسري على التحصيل الدراسي لدى التلميذات. Summary of the study in English Our study aimed to reveal the relationship of domestic violence and academic achievement among middle school students, and for this purpose, a sample of 70 students studying in Bahi Abdel Razzaq Intermediate School in Raguiba Al Wadi was tested. Physical violence directed at children within the family and its relationship to academic achievement Verbal violence directed at children within the family and its relationship to academic achievement We also followed the descriptive approach in our study, and we do not forget also a group of studies, and after calculating the psychometric characteristics and SPSS, we reached a set of results showing that there is no effect of domestic violence on the academic achievement of female students
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: العنف الأسري، La violence domestique, Domestic violence; التحصيل الدراسي، résultat scolaire, Academic achievement; المراهقة، adolescence